PENGARUH PENGGUNAAN APLIKASI SISTEM KEUANGAN DESA, SISTEM PENGENDALIAN INTERN PEMERINTAH, DAN KOMPETENSI APARATUR DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (Studi Kasus Pada Pemerintah Desa di Kabupaten Simalungun) - Yolanda Pinarsinta Silalahi; Haryanto Haryanto (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of the use of the Siskeudes application, the government's internal control system, and the competence of village government officials on the accountability of village fund management. This is a quantitative study with primary data obtained through the distribution of questionnaires to respondents. The respondents in this study consisted of village officials, namely village heads and finance officers in Simalungun Regency, North Sumatra Province. The research sample consisted of 150 village officials in Simalungun Regency. The sampling technique used was purposive sampling. The analysis technique used to test the hypothesis is multiple linear regression using SPSS version 29 as the analysis tool. The results of the study showed that the use of the Siskeudes application and the government's internal control system does not affect the accountability of village fund management. The competence of government officials had a positive effect on the accountability of village fund management.